Genetics of bone biology and skeletal disease - Thakker, R. V. (Elsevier/Academic Press, 2013)
This book identifies and analyzes the genetic basis of bone disorders in humans and demonstrates the utility of mouse models in furthering the knowledge of mechanisms and evaluations of treatments. The book is aimed at all students of bone biology and genetics, and with this in mind, it includes general introductory chapters on genetics and bone biology and more specific disease-orientated chapters, which comprehensively summarize the clinical, genetic, molecular genetic, animal model, functional and molecular pathology, diagnostic, counselling and treatment aspects of each disorder. Saves academic, medical, and pharma researchers time in quickly accessing the very latest details on a broad range of genetic bone issues, as opposed to searching through thousands of journal articles. Provides a common language for bone biologists and geneticists to discuss the development of bone cells and genetics and their interactions in the development of disease. Researchers in all areas bone biology and genetics will gain insight into how clinical observations and practices can feed back into the research cycle and will, therefore, be able to develop more targeted genomic and proteomic assays. For those clinical researchers who are also MDs, correct diagnosis (and therefore correct treatment) of bone diseases depends on a strong understanding of the molecular basis for the disease.